Sex differences in cardiopulmonary responses to exercise - Smith, Joshua Richard (Kansas State University, 2017)
The overall aim of this dissertation is to further understand sex differences in the cardiopulmonary responses during exercise in younger and older individuals. Emphasis is directed towards the influence of sex in modulating respiratory muscle blood flow and the inspiratory muscle metaboreflex. The first investigation of this dissertation (Chapter 2) demonstrated that sex differences do not alter respiratory muscle blood flow at rest or during exercise. The second investigation (Chapter 3) demonstrated that sex differences exist in the cardiovascular consequences of the inspiratory muscle metaboreflex. Specifically, premenopausal women, compared to age-matched men, exhibited attenuated increases in mean arterial pressure and limb vascular resistance as well as decreases in limb blood flow during inspiratory muscle metaboreflex activation. In Chapter 4, we demonstrated that postmenopausal, compared to pre-menopausal, women exhibit greater increases in mean arterial pressure and limb vascular resistance and decreases in limb blood flow during activation of the inspiratory muscle metaboreflex. Furthermore, no differences in the cardiovascular consequences were present between older men and women or younger and older men with activation of the inspiratory muscle metaboreflex. These data suggest that the tonically active inspiratory muscle metaboreflex present during maximal exercise will result in less blood flow redistribution away from the locomotor muscles in pre-menopausal women compared to postmenopausal women, as well as younger and older men. In conclusion, sex differences in young adults incur a major impact in the cardiovascular consequences during inspiratory muscle metaboreflex activation, while not modifying respiratory muscle blood flow.
Keywords: Blood flow; Metaboreflex; Sex differences